Canal transportation caused by one single-file and two multiple-file rotary systems: A comparative study using cone-beam computed tomography - Eshagh Ali Saberi; Narges Farhad Mollashahi; Forugh Farahi (Ariesdue, 2018)
Aim: This ex-vivo study aimed to compare canal transportation in mesio-buccal canal of mandibular first molars prepared with Mtwo and Revo-S multi-file and Neoniti single-file nickel-titanium (Ni-Ti) rotary systems using cone-beam computed tomography (CBCT). Methodology: CBCT scans were obtained from 60 extracted mandibular first molars and the teeth were randomly divided into three groups. Mesio-buccal canal of mesial root was prepared with Revo-S, Neoniti or Mtwo rotary systems according to the instructions of the manufacturers. Post-operative CBCT scans were also obtained. A single operator performed canal preparations while another operator blinded to the group allocation of teeth did the measurements. Data were analyzed using SPSS 20. The mean and standard deviation (SD) of the amount of canal transportation were calculated and compared between the groups using the Friedman test (P ≤ 0.05). Results: No significant difference was noted in canal transportation among the groups in the middle and apical third (P > 0.05). The rotary single-file instrument caused significantly greater canal transportation in the coronal third. Conclusion: No significant difference exists among different rotary systems in the amount of canal transportation caused in the middle and apical third of the mesio-buccal canal in mandibular first molars. Although all rotary files caused some degrees of canal transportation, the rotary single-file instrument caused significantly greater canal transportation than the multiple-file sequences in the coronal third. Riassunto: Obiettivi: Questo studio ex-vivo ha lo scopo di confrontare il trasporto canalare nel canale mesio-buccale di primi molari mandibolari preparati con i sistemi rotanti in nichel-titanio (Ni-Ti) Mtwo e Revo-S ed il sistema mono-strumento Neoniti, utilizzando la tomografia computerizzata a raggio conico (CBCT). Materiali e metodi: Le scansioni CBCT sono state ottenute in 60 primi molari mandibolari estratti e i denti sono stati suddivisi in tre gruppi. Il canale mesio-buccale della radice mesiale è stato preparato con sistemi rotanti Mtwo, Revo-S o Neoniti seguendo le istruzioni del produttore. Sono state quindi ottenute scansioni CBCT post-strumentazione. Un singolo operatore ha eseguito le preparazioni dei canali mentre un altro operatore ha effettuato le misurazioni. I dati sono stati analizzati utilizzando SPSS 20. La media e la deviazione standard (SD) della quantità di trasporto canalare sono stati calcolati e confrontati tra i gruppi usando il test Friedman (P ≤ 0.05). Risultati: Nessuna differenza significativa è stata osservata tra i gruppi nel trasporto dei canali nel terzo medio e apicale (P > 0.05), ma la tecnica mono-strumento ha causato un trasporto più significativo del canale nel terzo coronale. Conclusioni: Nessuna differenza significativa è stata riscontrata tra i diversi sistemi rotanti nella quantità di trasporto canalare nel terzo medio e apicale nel canale mesio-buccale di primi molari mandibolari. Anche se tutti i file rotanti hanno causato un certo grado di trasporto del canale, la tecnica mono-strumento rotante ha causato un trasporto del canale nel terzo coronale significativamente maggiore rispetto alle sequenze di file multipli. Keywords: Canal transportation, Nickel-titanium, Rotary files, CBCT, Parole chiave: Trasporto canalare, Nichel-titanio, Strumenti rotanti CBCT